The role of pedagogical and psychological conditions in the formation of information analysis skills and qualifications of future teachers - Nafisa Muratova (FAN VA TA’LIM INTEGRATSIYASI (INTEGRATION OF SCIENCE AND EDUCATION), 2024)
This article reveals the role and significance of pedagogical and psychological conditions for increasing interest in independent learning, developing the skills and competencies of information analysis among future teachers.